Influence of spousal educational disparities on intimate partner violence (IPV) against pregnant women: a study of 30 countries - M. D. Nahid Hassan Nishan; M. Z. E. M. Naser Uddin Ahmed; Saidur Rahman Mashreky; Koustuv Dalal (Scientific Reports)
Abstract Intimate Partner Violence (IPV) during pregnancy poses a serious threat to maternal health, particularly in low- and lower-middle-income countries (LMICs). Despite these known risks, the role of spousal educational differences in IPV during pregnancy remains poorly understood. This study aimed to examine this influence, analyzing data from multiple countries across five continents. This study utilized data from Demographic and Health Surveys (DHS) focusing on lower and LMIC countries. DHS employs two-stage sampling to gather comprehensive health data. Thirty countries from five regions were selected. Covariates like husband’s age, residence, wealth, education, husband’s working status, husband’s education, and spousal educational gap were considered. Cross-sectional survey design was considered. Chi-square test was done to find the association between IPV and covariates. Binary logistic regression was used to assess whether the independent variable is related to spousal educational disparity and other covariates of IPV during pregnancy. Out of 152,643 (weighted) pregnant women from all five continents, 8357 (weighted) experienced IPV during pregnancy. IPV is most prevalent in Papua New Guinea (17.01%; 95% CI 15.76–18.38%)), while least prevalent in Cambodia (0.99%; 95% CI 0.88–1.10%)). Overall, the IPV prevalence was (5.47%; 95% CI 5.30–5.65%)). Educational disparity and socioeconomic factors play a significant role in encountering IPV during pregnancy. This study revealed complex, region-specific effects on violence likelihood, emphasizing implications for policymakers and practitioners addressing IPV. Education disparity emerged as a significant factor; lower-educated couples exhibit increased abusive behavior.